Diagnostic thoracic ultrasound imaging – An exploration of respiratory physiotherapists' interest and use in clinical practice: A national survey - Hayward, Simon (Ultrasound, 2019)
INTRODUCTION: Physiotherapists are learning to perform diagnostic thoracic ultrasound but it is currently unknown how they are learning, how they are using thoracic ultrasound in their practice, or any factors affecting the implementation of thoracic ultrasound into practice. The aim of this survey was to explore the use of thoracic ultrasound by physiotherapists. This information could be used to aid training and implementation strategies to assist physiotherapists to integrate thoracic ultrasound safely into their practice. METHODS: A questionnaire comprising of open/closed questions was distributed to respiratory physiotherapist. Distribution was at three national study days and via a specialist newsletter containing a link to a SurveyMonkey™ questionnaire. RESULTS: A total of 133 questionnaires were returned with 31 reported that they used thoracic ultrasound imaging and 101 reporting they did not. The most common roles of thoracic ultrasound in practice were to: enhance the ability to differentially diagnose respiratory pathologies, aid respiratory assessment and support clinical reasoning. Of the 133 respondents, 58 reported that they had undertaken training in thoracic ultrasound imaging and 75 had not. The most common factors identified regarding thoracic ultrasound implementation were team support, ultrasound machine availability/cost, time pressures and mentor availability. DISCUSSION: This survey has provided an understanding of thoracic ultrasound practice amongst respiratory physiotherapists in the UK. The survey results demonstrated the barriers that inhibit current practice and highlighted the importance of mentor support. There was a good understanding by all respondents regarding the clinical application of thoracic ultrasound. These findings are being used to develop professional guidance and ensure safe practice of thoracic ultrasound.